2017
DOI: 10.1111/jerd.12292
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Visual Shade Matching in Dentistry

Abstract: The ability to understand and distinguish color differences in VSM is critical in clinical dentistry. Variation in shade perception due to observer gender can be minimized using additional observers and/or improving shade matching ability. (J Esthet Restor Dent 29:E15-E23, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
2
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 40 publications
(150 reference statements)
2
57
2
4
Order By: Relevance
“…Due to this limitation, CIEDE2000 color difference metric ( ΔE00) was developed. Recent studies that compared both metrics have demonstrated that ΔE00 presented a better correlation with visual perception than ΔEnormalanormalb. Therefore, the present study used ΔE00 to evaluate color stability of RC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to this limitation, CIEDE2000 color difference metric ( ΔE00) was developed. Recent studies that compared both metrics have demonstrated that ΔE00 presented a better correlation with visual perception than ΔEnormalanormalb. Therefore, the present study used ΔE00 to evaluate color stability of RC.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies 15,[18][19][20] that compared both metrics have demonstrated that DE 00 presented a better correlation with visual perception than DE Ã ab . Therefore, the present study used DE 00 to evaluate color stability of RC.…”
Section: Discussionmentioning
confidence: 99%
“…The parametric factors, K L , K C , K H are correction terms for variation in experimental conditions. Under reference conditions, they are all set at 1 …”
Section: Methodsmentioning
confidence: 99%
“…Under reference conditions, they are all set at 1. [46][47][48] The data were compared with thresholds for color perceptibility (PT) and acceptability (AT). 27 The supplementary data file rec-…”
Section: Color Calculationsmentioning
confidence: 99%
“…The traditional belief of females being better than males in shade selections are reported by many authors but there are also diametrically opposite and neutral views …”
Section: Introductionmentioning
confidence: 99%